Stable water isotopes (δ18O) of ice core EDML from 2416 m to 2773.5 m - Hans Oerter; Hanno Meyer; Frank Wilhelms; Florian Painer (PANGAEA, 2025)
The European Project for Ice Coring in Antarctica (EPICA) focused on the drilling of two deep ice cores, the first at Dome C (EDC) and the second at Kohnen station (75°00 extquotesingle S, 0°04 extquotesingle E) in Dronning Maud Land (EDML). This dataset presents the stable water isotopes (δ18O) of the EDML ice core from 2416 m to 2773.5 m in 0.5 m resolution. Ice samples were measured at the Alfred Wegener Institute in Bremerhaven and Potsdam using mass spectrometry. This dataset can be seen as an extension to EPICA Community Members (2010). However, note that the EDML ice core is dated down to approx. 2416 m depth because the match between EDML and EDC becomes ambiguous further down (Ruth et al., 2007).